Analysis According To Time And Forms Of Goals In The 2016 UEFA European Football Federation Championship - Kaplan, Abdurrahim; Bostanci, Ozgur; Mayda, M.Hakan; Satici, Arif; Ceylan, Levent; Yazici, Omer Faruk (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
The aim of this study is to analyze the time, form and how the 108 goals scored and defeated according to the outbreak of 51 games played in the 2016 UEFA European Football Championship. The data of the study were obtained from Prozone brand performance and match analysis program. In the study, the team can not qualify of the group (n:8) and qualify of the group (n:16); the total number of goals scored, the time of goals, the formation of the goals, and the technique of the strokes used. The Independent Samples T-Test was applied to examine the difference between the groups in the SPSS 20.0 program (p<0.05). According to the average of goals per game meaningfulness was observed (p<0,001) there was a significant difference between the teams that qualified of the group (1.22±0.41) and those who did not (0.46±0.27). The time zones in the scored and conceded goals of the team qualified of the group and those who did not, significant differences were observed between groups at 0-15, 30-45, 45-60 min in scored goals (p<0.05), no significant difference was found other time periods. In the competition it was determined that most goals were between 75-90 min (1.50±1.26). While the significance of the goals scored from the left and the right sides among the groups was determined (p<0.05), it was not found goal from the middle (p<0.05). Both in the penalty area and the penalty area outside goals, teams quaified of group were found to have more goals. According to results, in addition to increasing the tactical richness in the offensive area, the national teams and trainers must also prepare the team by analyzing the previous champions well so that the national teams can reach more goals in the championship.